EFEKTIFITAS TERAPI AKTIVITAS KELOMPOK (TAK) STIMULUS PERSEPSI TERHADAP HALUSINASI PADA PASIEN SKIZOFRENIA PARANOID DI RSJKO SOEPRAPTO BENGKULU TAHUN 2010 - Pardosi, Sariman (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
The most frequent type of schizophrenia is paranoid schizophrenia, whereas in patients with schizophrenia have common criteria and experiencing hallucinations or delusions (Suseno, 2001). Incidence of paranoid schizophrenia in RSJKO Soeprapto Bengkulu in 2008 was (58.84%) and in 2009 was (68.44%) (Medical Record, RSJKO Soeprapto, 2010). Paranoid schizophrenic with hallucinations and panic can act led to the occurrence of suicide or homicide. (Suseno, 2001). Nursing actions appropriate to address a group hallucination is a therapeutic group activities (TAK) (Siahaan HB, 1999). The purpose of research is known influence of group activity therapy (TAK) stimulation perception to hallucinations in RSJKO Soeprapto Bengkulu in 2010.Design research is an experiment: pre and post test. The population was all patients with paranoid schizophrenia who were treated at RSJKO hallucinations Soeprapto Bengkulu, on July 1 to August 31 in 2010, totaling 38 people. Purposive sampling technique with sampling. Analyses were performed by univariate and bivariate frequency distribution with one sample.T test, with α = 5%.The results were: ther’s a relationship bof group activity therapy (TAK) stimulation perception: recognition hallucinations (p = 0.00), controlling hallucinations (p = 0.00), preparation of the schedule of events (p = 0.01), the way drinking either drug (p = 0.00).It is hoped that nurses in RSJKO more intensified activities group activity therapy (TAK) regularly, at least once a week for paranoid schizophrenia patients with hallucinations. In order to speed up eliminating hallucinations and shorten the lengthofthepatient.